The stress-strain state of horizontal joints of wall panels - Anatolii Kostyuk; Dariya Kovtunenko; Aleksei Kovtunenko (Tehnički Glasnik, 2019)
The article is devoted to the experimental and numerical research of the stress-strain state of wall panels joints from foam concrete of natural hardening. The eccentricity of the load and the quantity of indirect reinforcement meshes are adopted as factors that have a significant effect on the stress-strain state of the joint elements. The load in the experimental research and numerical simulation was applied in steps of 0.1 of the estimated value of the destructive force. Numerical modelling was carried out with consideration of the physical nonlinearity of the wall panel materials. A significant increment in the displacement of the design scheme nodes at the current loading stage was taken as a destruction criterion in numerical modelling. It is noted that the installation of indirect reinforcement meshes leads to a reduction of transverse deformations of the wall panel, but does not significantly affect the bearing capacity of the joint.